“Remédio da hora”: uma aplicação android para controle de medicamento - Prato, Jonatas Sartorelli (Universidade do Vale do Rio dos Sinos, 2014)
This work aims at presenting a mobile application for control and management of medicine, with notification function based on time and also the quantity of drugs in stock; price research funcionality and search pharmacies based at position user. This paper initially the motivation, goals and concepts that underlie this article. Existing related works in the market are also analysed and performs a comparison with the proposed work. Then, we propose “MedControl” application in order to meet the listed requirements and make life easier for users using the Android platform, assisting them in medical treatments with prescription medications. Finally, the results obtained in the evaluation of acceptance of the application made by the users are presented, along the concluding remarks and future works.
Keywords: Sistema de controle de medicamento; Computação móvel; M-Health; Android; Dispositivos móveis; Farmácias; Application for control of medicine; Mobile computing; Pharmacies